PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING PADA TOKO KINANTHA KIDS STORE KOTA BALIKPAPAN - Juhairiyah; Sukimin; Indriastuty, Nina (MEDIA RISET EKONOMI [MR.EKO], 2024)
The Objective of the research to the effect of Service Quality on Customer Loyalty with Customer Satisfaction as an intervening variable. This research was conducted on customers who have visited and made transactions at least twice.  Sampling technique with non probability sampling. The analysis method used in this research is regression analysis of the causal step method and questionnaires as a means of collecting respondent data and then processed with the help of the SPSS Statistics programme with a sample size of 315. The data analysis techniques used in this study are validity test, reliability test, normality test, F-test, t-test, R-test, regression analysis of intervening variables and sobel test to see how much the independent variable affects the related variable through the intervening variable. Based on the results obtained from this study, service quality has a positive and significant influence on customer loyalty with customer satisfaction as an intervening variable at Kinantha Kids Store Balikpapan City. Service quality, customer satisfaction have an influence of 18.9% on customer loyalty, while the remaining 81.1% is influenced by other variables not examined in this study.